Medical challenge posed by retroperitoneal fibrosis : case reports and literature review (2020)
Idiopathic retroperitoneal fibrosis (RPF) is a rare fibro-inflammatory disease, with a low incidence worldwide, which occurs around the abdominal aorta and the iliac arteries. It spreads through the retroperitoneum causing ureteral obstruction with associated renal failure and obstruction of other adjacent structures. RPF can be idiopathic or secondary to neoplastic processes, infections, or medications. RPF is considered part of the spectrum of the disease related to immunoglobulin G4 (IgG4) and other autoimmune disorders. Occupational exposure to asbestos and tobacco smoke are important risk factors for the development of idiopathic RPF. The clinical picture is nonspecific, from pain to symptoms due to ureteral compression, this being the main complication associated. Imaging studies are essential in the diagnosis; computed tomography (CT) and magnetic resonance imaging (MRI) are the most reliable imaging modalities. The goal of treatment is to stop the progression of the fibroinflammatory reaction. The first line of treatment is usually with medical management. Biological agents, such as rituximab and infliximab, have also been used, even with scarce data in the literature. Surgery is usually performed to improve a ureteral obstruction and should always be accompanied by systemic steroid treatment. The conservative approach given by systemic therapy and ureteral stent placement or nephrostomies has been recommended, thus reserving surgical treatment for refractory cases. We present two clinical cases of idiopathic RPF, one of them associated with IgG4.